Blended Learning and Creativity-Based Learning for Promoting Mathematics Achievement and Information Technology Performance - Wannatida Yonwilad,; Unyaparn Sinlapaninman, (Journal of Educational Issues, 2024)
This study aimed to develop blended learning activities and creativity-based learning in the Mathematics for Computer Course (MCC), compare mathematics achievement in the MCC at a 70% threshold score, compare students’ information technology usage performance, and investigate students’ learning satisfaction. The participants were freshmen who enrolled in MCC at Kalasin University, academic year 2021. Purposive sampling was employed in the recruitment of 25 students. The research tools included: six activities in the MCC, multiple-choice achievement test with 30 items, the information technology competency assessment form, and a 15-item activity satisfaction scale. The statistics used in the data analysis are descriptive for calculating mean, standard deviation, and percentage, as well as one sample t-test for hypothesis testing. The findings indicated that the academic achievement of students representing 76.67% higher than the specified threshold of 70% with statistical significance at the 0.05 level. Students’ competency in using information technology is 81.67 percent, which is higher than the threshold and they were satisfied with learning approach.